2019
DOI: 10.3389/fimmu.2019.02830
|View full text |Cite
|
Sign up to set email alerts
|

Treating the Different Phenotypes of Behçet's Syndrome

Abstract: Behçet's syndrome (BS) is a multisystemic vasculitis, characterized by different clinical involvements, including mucocutaneous, ocular, vascular, neurological, and gastrointestinal manifestations. Based on this heterogeneity, BS can be hardly considered as a single clinical entity. Growing evidence supports that, within BS, different phenotypes, characterized by clusters of co-existing involvements, can be distinguished. Namely, three major BS phenotypes have been reported: (a) the mucocutaneous and articular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 97 publications
1
55
1
2
Order By: Relevance
“…Indeed, the predominant phenotypes have already been defined and are thought to be governed by different disease mechanisms requiring diversified treatment modalities. 23 Here we report the results of a retrospective study conducted on a series of 15 patients with the mucosal and articular phenotype of BS and treated with secukinumab. The observed effectiveness of secukinumab in this phenotype has a strong pathophysiological basis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the predominant phenotypes have already been defined and are thought to be governed by different disease mechanisms requiring diversified treatment modalities. 23 Here we report the results of a retrospective study conducted on a series of 15 patients with the mucosal and articular phenotype of BS and treated with secukinumab. The observed effectiveness of secukinumab in this phenotype has a strong pathophysiological basis.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of the disease, BS can involve the mucosa, skin, or eyes, vessels, nervous and gastrointestinal system [ 22 , 23 , 46 ]. Several cluster and association studies reported clusters of common overlapping involvements.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hussein et al reported that genital ulcers and systemic vasculitis were protective factors for the development of vision threatening eye disease [ 50 ]. We focused on BS patients with eye involvement since, each involvement has its own demographic and clinical characteristics, and also medical treatment and prognosis of each manifestation differs greatly [ 46 ]. Oezguen N et al have subjected neuro-Behçet’s disease for the analysis of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…For non-parenchymal disease with CVST, first-line therapy is also high-dose steroids with an oral taper but further immunosuppression is not usually necessary as relapses are uncommon [24]. Use of anticoagulation is debated given increased risk of bleeding, but a short course is advised (Grade C) [22,25,26]. Recurrence of CVST is rare if systemic inflammation is well controlled, and accordingly, long-term anticoagulation is not indicated [24,25].…”
Section: Behcet's Diseasementioning
confidence: 99%
“…Use of anticoagulation is debated given increased risk of bleeding, but a short course is advised (Grade C) [22,25,26]. Recurrence of CVST is rare if systemic inflammation is well controlled, and accordingly, long-term anticoagulation is not indicated [24,25]. Similarly, recurrence of dissection in the setting of vasculitis may be prevented with early pulse steroids [29].…”
Section: Behcet's Diseasementioning
confidence: 99%